Associations Between Participant Ratings of PREP for Strong Bonds and Marital Outcomes 1 Year Postintervention. Issue 4 (6th April 2017) - Allen, Elizabeth S.; Post, Kristina M.; Markman, Howard J.; Rhoades, Galena K.; Stanley, Scott M.
Abstract : After completing a relationship education program, collecting participant evaluations of the program is common practice. These are generally used as an index of "consumer satisfaction" with the program, with implications for feasibility and quality. Rarely have these ratings been used as predictors of changes in marital quality, although such feedback may be the only data providers collect or have immediate access to when considering the success of their efforts. To better understand the utility of such ratings to predict outcomes, we evaluated links between participant ratings and changes in self-reported marital satisfaction and communication scores 1 year later for a sample of 191 Army couples who had participated in a relationship education program delivered by Army chaplains (PREP for Strong Bonds). Overall ratings of general satisfaction with the program and the leader did not predict changes in marital outcomes 1 year later, whereas higher ratings of how much was learned, program helpfulness, increased similarity in outlook regarding Army life, and helpfulness of communication skills training predicted greater change in communication skills 1 year later. Higher ratings of items reflecting intent to invest more time in the relationship, and increased confidence in constructive communication and working as a team with the spouse predicted greater increases in both marital satisfaction and communication skills 1 year later. The constructs of intention and confidence (akin to perceived behavioral control) suggest that the Theory of Planned Behavior may be particularly useful when considering which Army couples will show ongoing benefit after relationship education.